PELAKSANAAN PERATURAN MENTERI DALAM NEGERI NOMOR 26 TAHUN 2020 TENTANG PENYELENGGARAAN KETERTIBAN UMUM DAN KETENTERAMAN MASYARAKAT SERTA PERLINDUNGAN MASYARAKATDI KOTA SOLOK - Meita Lefi Kurnia, Henry Satria Dinata dan (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
Community involvement who are recruited voluntarily to participate in activities that are part of the Satlinmas, are entitled to increase their capacity to acquire knowledge and skills. To explore this, the author uses an empirical/sociological juridical approach and analyzed qualitatively. The results of this study can be concluded that the implementation of the Minister of Home Affairs Regulation Number 26 of 2020 in Solok City is that the Solok City Government has formed a Satlinmas with the Solok Mayor's Decree Number: 188.45-02-2021 with 148 Satlinmas members. Empowerment of Satlinmas such as social activities and as the Village Covid-19 Task Force. On average, Satlinmas members are still of productive age, with the lowest education being junior high school graduates and most of the Satlinmas members are farmers and traders. The constraints are that the capacity building of Satlinmas members has not been maximized, the younger generation's lack of interest in joining Satlinmas, and the District/City and District Linmas Task Force has not yet been formed. The solution must be to carry out capacity building for Satlinmas members, grow the interest of the younger generation to want to join Satlinmas members and form a Linmas Task Force in regional and sub-district governments to facilitate coordination and guidance on the empowerment of Satlinmas in the context of peace and public order.